WRITING ANXIETY IN EFL STUDENTS: PERSONALITY TRAITS PERSPECTIVE - Benni Ichsanda Rahman Hz (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2023)
This study is aimed to investigate the distinction level of writing anxiety between introvert and extrovert English-language (EFL) students. A qualitative case study methodology was utilized to explore a phenomenon within its authentic setting. A modified edition of the Second Language Writing Anxiety Scale (SLWAS) questionnaire was developed by Y.-S. Cheng (2004). The study's participants were categorized based on their personality traits as either introverts (n=29) or extroverted (n=29), categorized according to their personality types. The results showed that introverted individuals have a higher level of anxiety in writing context, with an average score of 3.38. In addition, the results showed the relationship between personality traits and writing anxiety among EFL students. In conclusion, this study found that personality traits like introversion and extraversion can affect writing anxiety and performance. It's important to recognize and address these variations to support individuals with different personality types in improving their writing skills and reducing writing-related anxiety.